Effects of a novel hepatitis B anti-viral drug E-CFCP in renal organic acid transporters - Misaki Ishibane; Hirofumi Hashimoto; Meika Kaneko; Shota Saito; Sangjon Pae; Shinpei Saito; Yoshie Reien; Yuri Hirayama; Nobuyo Higashi-Kuwata; Hiroaki Mitsuya; Naohiko Anzai (Elsevier, 2022)
Currently, the emergence of drug resistance is an important issue in the treatment of hepatitis B virus (HBV). Recently, our collaborating group developed a novel long-acting anti-HBV drug, E-CFCP. However, until this study, the effects of E-CFCP in the kidney have remained unclarified. Using cell viability and uptake assays, we examined the effects of E-CFCP on the function of renal organic anion transporters (OATs). No cytotoxicity was shown related to the E-CFCP in the renal OATs in either assay. Thus, this study suggested that E-CFCP may be a novel, excellent candidate drug for the treatment of drug-resistant HBV.